The giant genome of lily provides insights into the hybridization of cultivated lilies - Yuwei Liang; Qiang Gao; Fan Li; Yunpeng Du; Jian Wu; Wenqiang Pan; Shaokun Wang; Xiuhai Zhang; Mingfang Zhang; Xiaoming Song; Linlin Zhong; Fan Zhang; et al. (Nature Communications)
Abstract Lilies are economically important monocots known for their ornamental flowers, bulbs, and large genomes. The absence of their genomic information has impeded evolutionary studies and genome-based breeding efforts. Here, we present reference genomes for Lilium sargentiae (lily, 35.66 Gb) and Gloriosa superba (flame lily, 5.09 Gb). The giant lily genome is shaped by recent long terminal repeat retroelements. Phylogenetic analysis reveals diverse, independent origins of lily cultivars. Gene families involved in sucrose and starch metabolism are significantly expanded in the lily genome. Key homologs of XTH22, SOC1, and AP1/FUL-like genes regulate the development, bud growth transition, and floral bud growth transition of lily bulbs. Colchicine biosynthetic gene clusters are identified in G. superba but are absent in L. sargentiae, highlighting independent colchicine evolution in Colchicaceae. These genomic insights enhance understanding of Liliales evolution, providing a foundation for future breeding and molecular research.